Work Psychology and Occupational Health (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue focuses on topics such as the effect of the pandemic on the working environment; the relationship between the pandemic and the psychological effects on workers; and maintenance and/or measures for workers’ health (especially mental health) during the pandemic. The key items for the above objectives are the introduction and increase of telework and online operations; changes in the working environment, such as reduced working hours, dismissal, and the effects of unemployment; changes such as increased stress and decreased coping strategies among workers; increased loneliness and isolation, as well as decreased opportunities for communication—including opportunities for employees to meet for mental health resources—and an increase in the need for self-care as a stress-coping method that can be practiced by one person. It also includes hands-on experience in dealing with the increase in serious stress and loneliness via strong support at the organizational and individual levels.